WOMEN AND MIGRATION: A LITERARY AND SOCIOLOGICAL ANALYSIS - Behiye Arabacioğlu (PUPIL: International Journal of Teaching, Education and Learning, 2026)
The works of two second-generation Turkish women writers who migrated to Germany are examined in terms of the social and cultural contexts of identity, culture, and family. How these social and cultural contexts are represented in the literary narratives is demonstrated through selected quotations from the texts. The primary sources of this study are Hatice Akyün’s Einmal Hans mit scharfer Soße and Nilgün Taşman’s Ich träume deutsch und wache türkisch auf. As literary and sociological documents, these works are analyzed through a comparative method focusing on character construction, language use, and narrative structures. Using this comparative analytical approach, the study evaluates linguistic choices and cultural references in the works of Akyün and Taşman in order to explore the social and cultural construction of identity and to assess the different strategies of belonging—whether to one or both cultures—employed during the migration process. This method also incorporates theoretical frameworks from the sociology of literature and cultural identity studies to identify the language practices and cultural affiliation strategies adopted by the migrant female subject who negotiates her identity between two cultures. The migration process brings about multiple transformations of identity, shifts in social roles, and changes in the ways individuals build connections with others. Migrants—particularly women—encounter various challenges that render these transitions visible as they interact with both their heritage culture and the cultural dynamics of their new living environment. These challenges include the reconfiguration of familial roles, expectations related to gender, and the ways in which individuals construct or reconstruct their identities. Women, throughout the migration experience, act not only as carriers of cultural traditions but also as agents of cultural change and adaptation, actively negotiating and reshaping their identities between the two cultures. The unique contribution of this study lies in its comprehensive and interdisciplinary examination of the network of relations among migration, women, and family in the works of Akyün and Taşman. It offers both a theoretical model that explains how the identity of a migrant woman is reconceptualized in relation to her family and empirical findings on the nature of intercultural contact and the gendered division of social roles.